Autonomy Learning in The Praxis of Language Education: A Systematic Review - Rina Husnaini Febriyanti (Universitas Indraprasta PGRI, 2021)
The rapid increase of technology has transformed the praxis of language education and linked to the construct of autonomy learning. It is believed that the great technology accommodated the language learners to achieve their goals and aims. However, this statement is still debatable in language instruction. Given the previous consideration, the purpose of this study was to explore by reviewing 23 articles focusing on the autonomy learning issues that scholars or researchers discussed in their papers. The used research method in this manuscript was a systematic review. This study investigated six prior subheadings: the change number varies by year, the foci and purposes, countries where the articles were published, the applied research methods and data collection tools, the occupied sample group, sample size, and the adopted method theoretical frameworks and dimensions. The data collection was taken by categorizing the six subheadings and analyzing them by presenting bar graphics, figure maps, and tables. The study revealed various insights related to autonomy learning, such as still in the recent trending issue, applicable in multiple approaches, potentially in the sundry of theoretical frameworks, elaborating in numerous dimensions, with ample applied research methods, and so forth. In addition, the implication of this study considerably can be useful for the freshmen or sophomore researchers to gain state of the art or novelty before conducting research or publishing papers specifically on the topic of autonomy learning in the praxis of language education.Keywords: Autonomy Learning; Language Education; Systematic Review